Impacts of the Building (Earthquake-prone Buildings) Amendment Act 2016 on the retention of historical buildings in New Zealand's provincial city-centres : towards promoting seismic resilience through adaptive reuse : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Engineering, Massey University, Auckland, New Zealand - Aigwi, Itohan Esther (Massey University, 2020)
The impacts of the increasing scale of earthquake disasters on New Zealand's historical buildings are becoming so prevalent to the extent of threatening the stability and existence of provincial urban areas, hence, resulting in local resilience emergencies. This thesis is designed to promote seismic resilience and city-centre regeneration through the retention of earthquake-prone historical buildings for New Zealand’s provincial regions that have an abundance of underutilised earthquake-prone commercial historical buildings in their city-centres. No prior research has explored the main factors that contribute to the loss of historical buildings in New Zealand’s provincial city centres as a result of the Building (Earthquake-prone Buildings) Amendment Act 2016, and how the retention of the buildings can be improved. This thesis aims to address such inadequacy by identifying representative New Zealand’s provincial cities and the contributing factors to their inner-city decline with links to the impact of the Building (Earthquake-prone Buildings) Amendment Act 2016. The applicability of the adaptive reuse approach (i.e., the change of use of an existing building) is also explored as a sustainable approach to retain underutilised commercial earthquake-prone historical buildings and promote seismic resilience and city-centre regeneration, by developing a performance-based framework to improve the adaptive reuse decision-making process. Using a sequence of qualitative and quantitative research enquiry modes, the research question was answered to justify the overall aim of the thesis. The findings revealed Whanganui and Invercargill as representative examples of New Zealand’s earliest cities currently experiencing a decline in their city centres, and also identified socio-economic and regulatory factors that may have contributed to their decline. Correspondingly, the impacts of the actions (or inactions) of local councils and building owners regarding compliance with the Building (Earthquake-prone Buildings) Amendment Act 2016 have also been addressed. Examining the importance of heritage buildings in New Zealand and the allocation of government funding in the form of grants for the retention of these buildings imply that though New Zealand’s government heritage grant systems are the most extensive non-regulatory incentives for the protection of built heritage, most of the grants are allocated to the bigger cities with the least per capita distribution of heritage buildings. The provincial regions with the most per capita ratio may continue to struggle to conserve their oversupply of heritage buildings if a disproportionately lower allocation of heritage protection grants to provincial regions continues to happen. Findings from this thesis also revealed the main parameters (economic sustainability, built-heritage conservation, socio-cultural aspects, building usability, and regulatory aspects) for a performance-based framework to prioritise optimal underutilised commercial earthquake-prone historical buildings for adaptive reuse. The findings established the practicality of the validated framework in balancing the diverse interests of all stakeholders in an adaptive reuse decision-making process. The consensus among the multidisciplinary stakeholder group was acknowledged to be consistent and insensitive to reasonable changes in weighting. An in-depth understanding of the characteristics of adaptive reuse stakeholders (i.e., identified as investors, producers, regulators and users) and the effectiveness of collaborative rationality among the diverse stakeholders was also found to improve: (i) active participation of stakeholders for future adaptive reuse prioritisation exercises; (ii) public consciousness and knowledge regarding adaptive reuse issues; (iii) transparency and accountability among the stakeholders; (iv) trust and organised networking among the stakeholders; and (v) legitimacy and quality of adaptive reuse decisions. Accordingly, the efficacy of adaptive reuse has been justified in this thesis as a sustainable approach to renegotiating seismic resilience and vitality in the city centres of Whanganui and Invercargill. This thesis significance updates both the practical and theoretical understanding of seismic resilience and city-centre regeneration through the adaptive reuse of underutilised historical buildings in New Zealand’s provincial areas to mitigate the impacts of the Building (Earthquake-prone Buildings) Amendment Act 2016, hitherto lacking. As a practical significance, the performance-based framework from this thesis guided Whanganui district council, as both a planning and measurement tool to prioritise and conserve underutilised earthquake-prone commercial historical buildings in their city-centre for adaptive reuse, while balancing the diverse interests of all relevant stakeholders. Also, findings from this thesis are of relevance to the theoretical body of knowledge as a guide for other researchers who are pursuing closely related research topics to that of this thesis.
Keywords: New Zealand; Building (Earthquake-prone Buildings) Amendment Act 2016; Buildings; Earthquake effects; Law and legislation; Historic buildings; Conservation and restoration; Whanganui; Invercargill; 330103 Architectural heritage and conservation; 400506 Earthquake engineering